Memory effect behavior with respect to the crystal grain size in the organic-inorganic hybrid perovskite nonvolatile resistive random access memory. Issue 1 (December 2017) - Heo, Jin; Shin, Dong; Moon, Sang; Lee, Min; Kim, Do; Oh, Seol; Jo, William; Im, Sang
Abstract The crystal grain size of CH3 NH3 PbI3 (MAPbI3 ) organic-inorganic hybrid perovskite (OHP) film was controllable in the range from ~60 nm to ~600 nm by non-solvents inter-diffusion controlled crystallization process in dripping crystallization method for the formation of perovskite film. The MAPbI3 OHP non-volatile resistive random access memory with ~60 nm crystal grain size exhibited >0.1 TB/in2 storage capacity, >600 cycles endurance, >104  s data retention time, ~0.7 V set, and ~−0.61 V re-set bias voltage.